Financial Literacy and Financial Attitude on Financial Satisfaction: Mediating Effect of Financial Well-Being - Rinny Meidiyustiani; Heni Iswati (Institut Bisnis dan Informatika Kesatuan, 2025)
The involvement of women in the MSME sector has grown markedly, with female entrepreneurs playing a significant role in generating household income, creating employment opportunities, and supporting national economic development. Despite their important contributions, many women entrepreneurs continue to face challenges in financial management, emphasizing the need for strong financial literacy and constructive financial attitudes to achieve financial satisfaction and sustainable economic stability. This study examines the impact of financial literacy and financial attitudes on financial satisfaction, with financial well-being serving as a mediating variable. The research targets women-owned MSMEs in Indonesia, which are critical to the nation’s economic progress. Employing a quantitative approach with an explanatory research design, data were collected through a survey of 90 female entrepreneurs. Path analysis using Smart-PLS was conducted to test the proposed hypotheses. Findings reveal that financial literacy and financial well-being significantly enhance financial satisfaction, while financial attitudes do not exert a direct effect. Furthermore, financial well-being effectively mediates the influence of financial literacy on financial satisfaction but does not mediate the relationship between financial attitudes and satisfaction. These results highlight the importance of financial literacy in guiding financial decision-making and improving satisfaction among women MSME owners.